2021
DOI: 10.1038/s41396-020-00836-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial microbiota similarity between predators and prey in a blue tit trophic network

Abstract: Trophic networks are composed of many organisms hosting microbiota that interact with their hosts and with each other. Yet, our knowledge of the factors driving variation in microbiota and their interactions in wild communities is limited. To investigate the relation among host microbiota across a trophic network, we studied the bacterial microbiota of two species of primary producers (downy and holm oaks), a primary consumer (caterpillars), and a secondary consumer (blue tits) at nine sites in Corsica. To qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 74 publications
(100 reference statements)
1
25
0
Order By: Relevance
“…In support of this, a study on New Guinean birds demonstrated that the GM of smaller passerine species was less stable and more heterogenous than that of larger species, presumably because shorter guts and faster retention times can result in stronger ecological drift and a higher turn-over of bacterial species acquired from environmental sources [ 94 ]. As Seychelles warblers are insectivorous, bacterial species could be readily acquired from their insect prey [ 95 ] as well as from the surrounding environment. As such, differences in GM diversity across individuals could potentially reflect variable uptake from these sources.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a study on New Guinean birds demonstrated that the GM of smaller passerine species was less stable and more heterogenous than that of larger species, presumably because shorter guts and faster retention times can result in stronger ecological drift and a higher turn-over of bacterial species acquired from environmental sources [ 94 ]. As Seychelles warblers are insectivorous, bacterial species could be readily acquired from their insect prey [ 95 ] as well as from the surrounding environment. As such, differences in GM diversity across individuals could potentially reflect variable uptake from these sources.…”
Section: Discussionmentioning
confidence: 99%
“…Oviparous birds (class Aves) acquire their initial gut symbionts after hatching, although the sterile nature of eggs and the transfer of maternal microbiota during egg formation is still controversial [13]. Post-hatching, parental and nest microbiomes [14,15] along with diet [7,[16][17][18] and habitat [19][20][21][22][23] are thought to be the major factors shaping avian gut microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…In such a scenario, the consumption of insects would expand their microbial acquisition range, which resembles more that of a flying insect ( Figure 2B ). A transfer of microbes across predator-prey networks has been suggested for insectivorous birds and predatory insects ( Tiede et al, 2017 ; Suenami et al, 2019 ; Dion-Phénix et al, 2021 ). The mammalian microbiota is strongly influenced by species identity and type of diet, but an increase of invertebrate prey (i.e., insects) within the diet correlates with a decrease in bacterial alpha diversity compared to mammals with a primarily herbivorous lifestyle ( Knowles et al, 2019 ; Harrison et al, 2021 ).…”
Section: How Host Movement Shapes the Host Microbiotamentioning
confidence: 99%